2015
DOI: 10.1158/2326-6066.cir-15-0015
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Induces, and Adenosine Suppresses, CXCR3-Cognate Chemokine Production and T-cell Infiltration of Lungs Bearing Metastatic-like Disease

Abstract: Despite immunogenicity, melanoma-specific vaccines have demonstrated minimal clinical efficacy in patients with established disease but enhance survival when administered in the adjuvant setting. Therefore, we hypothesized that organs bearing metastatic-like melanoma may differentially produce T-cell chemotactic proteins over the course of tumor development. Using an established model of metastatic-like melanoma in lungs, we assessed the production of specific cytokines and chemokines over a time-course of tum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 36 publications
2
40
0
1
Order By: Relevance
“…The role of CXCR3 and the ligands CXCL9 and CXCL10 in anti-tumor immunity is well established (29, 34, 57, 58). In a recent study, Mikuchi et.al elegantly demonstrated that CXCR3 mediated signalling to be a critical and an indispensable checkpoint for tumor antigen specific CD8 + T cells to traffic across the tumor vasculature for carrying out effective tumoricidal activity in mice and human melanoma (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of CXCR3 and the ligands CXCL9 and CXCL10 in anti-tumor immunity is well established (29, 34, 57, 58). In a recent study, Mikuchi et.al elegantly demonstrated that CXCR3 mediated signalling to be a critical and an indispensable checkpoint for tumor antigen specific CD8 + T cells to traffic across the tumor vasculature for carrying out effective tumoricidal activity in mice and human melanoma (29).…”
Section: Discussionmentioning
confidence: 99%
“…Among the immune cells, CD4 + T cells were considered the major producers of CXCL9 as well as IFNγ in the metastatic nodules in lung (34). While most myeloid cells can readily produce LTB 4 , the source of this BLT1 ligand in the B16 tumors remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…IFNγ can induce CXCL9-11 production from human melanoma cells in vitro [11]. These chemokines promote the migration of CXCR3 + T-cells into tumors [11], in murine models, expression of IFNγ in the TME enhances T-cell mediated anti-tumor immunity [25], and CXCR3 + T-cells have been demonstrated to mediate tumor rejection [12,26]. In patients, CXCL10 expression in the TME is associated with better T-cell infiltration, tumor control, and disease-free survival [2729].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies evaluated expression of individual HR ligands on tumor vasculature, and concluded that the expression of E-selectin (15,25), ICAM-1(15), CXCL9(20,21), and VCAM-1(19) was often low. Expression of VCAM-1 correlates with T-cell representation in several human cancers (16,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…LFA-1/ICAM-1 interactions are common mediators of leukocyte engagement with other cells and, not surprisingly, play an important role in entry into murine melanoma and human glioblastoma (1517). CXCR3 interactions with CXCL9/10 mediate entry into subcutaneous (SC) and intracranial murine melanomas (1820) and correlated with the representation of CD8 + T cells in melanomas growing in lungs (21). α 4 β 1 /VCAM-1 interactions are required for CD8 + T-cell accumulation in intracranial melanoma (22) and in SC melanoma following kinase inhibitor-induced VCAM-1 upregulation (19).…”
Section: Introductionmentioning
confidence: 99%